(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Barley; Nitrogen fertilizer; Nitrogen utilization Bangladesh j. genet. biotechnol. 5 (1&2): 19-21, 2004 (June & December)